Tactile acuity and left/right judgment performance in patients with knee osteoarthritis: A cross-sectional study - Ozgul, Sinem; Ozturk, Ozgul; Gulkesen, Arif (Elsevier, 2023)
Background: Left/right judgment task (LRJT) performance and tactile acuity are impaired in chronic pain con-ditions, however, evidence is limited for knee osteoarthritis (OA).Objective: To compare LRJT performance and the two-point discrimination threshold (TPDT) of chronic knee OA patients with asymptomatic knee and pain-free controls.Design: Cross-sectional study. Methods: Fifty knee OA patients and 50 age and gender-matched pain-free controls were assessed using the Recognize (R) application by displaying knee images and a digital caliper for the TPDT of the medial and lateral knee joint line.Results: TPDTs over the lateral joint line in symptomatic (mean difference [MD]: 13.59 mm; 95% confidence interval [CI]: 8.72, 18.46; d = 1.40) and asymptomatic knee (MD: 10.15 mm; 95% CI: 5.08, 15.22; d = 0.99) were significantly increased compared to pain-free controls. Similarly, TPDTs of the medial joint line were significantly increased in symptomatic (MD: 12.19 mm; 95% CI: 7.59, 16.79; d = 1.31) and asymptomatic knee (MD: 7.64 mm; 95% CI: 3.64, 11.64; d = 1.31) compared to pain-free controls. Patients with knee OA were less accurate (MD: 7.80%; 95% CI: 15.32,-0.27; d = 0.52) recognizing images of their symptomatic knee. No correlation was found between pain severity, pain duration, LRJT performance, and TPDTs. Post-hoc analysis revealed no differences in LRJT and TPDTs between patients with and without clinically relevant symptoms of central sensitization.Conclusion: Chronic knee OA is associated with increased TPDT for medial and lateral knee joint lines and decreased recognition accuracy performance which should be considered during treatment process.
Keywords: Knee osteoarthritis; Chronic pain; Tactile acuity; Implicit motor imagery